Abnormal gait and hypoglycorrhachia in a toddler with seizures - Maria Angeli; Eleni Vergadi; Georgios Niotakis; Maria Raissaki; Emmanouil Galanakis (Wiley, 2022)
ABSTRACT Introduction Glucose transporter type 1 (Glut1) deficiency syndrome is a treatable neurometabolic disorder characterized by seizures, developmental delay, and hypoglycorrhachia. Due to the rareness and non‐specific clinical manifestations, it is usually mis‐ or underdiagnosed. Case presentation We report the case of a toddler who presented with afebrile epileptic seizures and abnormal gait. Brain imaging and electroencephalogram were normal. Further investigation of the cerebrospinal fluid revealed hypoglycorrhachia that was the clue to the diagnosis of Glut1 deficiency syndrome and the initiation of treatment with ketogenic diet. Conclusion Our case highlights the importance of lumbar puncture while investigating a child with epileptic seizures and abnormal gait or developmental delay, in order not to miss treatable neurometabolic conditions, such as Glut1 deficiency syndrome.